Perancangan Mesin Sangrai Kacang Kulit Dengan Sisitem Pengluaran Tanpa Pengerukan Serta Analisis Simulasi Termal - Selfi Herrani; Rani Puspita Dewi (Politeknik Negeri Semarang, 2026)
Peanut is one of the agricultural commodities commonly utilized by Micro, Small, and Medium Enterprises (MSMEs) as raw material for roasted peanut products. In general, the roasting process in small-scale industries is still carried out conventionally using manual stirring over an open stove. This condition often causes operator fatigue, uneven roasting quality, and inefficient heat usage. Several previous studies have developed roasting machines to improve productivity; however, the product discharge process still requires manual scraping and the heating system tends to consume relatively high fuel energy. Therefore, this research aims to design a peanut roasting machine equipped with an automatic discharge mechanism without manual scraping and supported by a single-burner heating system. The study applied an engineering design method combined with numerical simulation using SolidWorks 2024 software. The research stages consisted of literature review, component calculation, three-dimensional modeling, mechanical simulation, thermal analysis, and evaluation of simulation results. Mechanical analysis was conducted to determine the structural performance of the roasting cylinder under rotational loads, while thermal simulation was used to evaluate heat distribution from the heat source to the roasting drum. The simulation results indicated that the designed machine was able to reduce operator workload, simplify the discharge process, and provide more stable heat distribution during roasting. Consequently, the proposed machine design is expected to increase productivity and operational efficiency in household-scale roasted peanut industries.